2017
DOI: 10.1111/joa.12689
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of neonates of the three major mammalian groups (monotremes, marsupials, placentals) and implications for the ancestral mammalian neonate morphotype

Abstract: The existing different modes of reproduction in monotremes, marsupials and placentals are the main source for our current understanding of the origin and evolution of the mammalian reproduction. The reproductive strategies and, in particular, the maturity states of the neonates differ remarkably between the three groups. Monotremes, for example, are the only extant mammals that lay eggs and incubate them for the last third of their embryonic development. In contrast, marsupials and placentals are viviparous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 152 publications
0
54
0
Order By: Relevance
“…Already Röse () proposed the secondary foramen was an adaptation to particular conditions of gestation and Runciman and colleagues (Runciman et al, ) suggested a role for the great duration of the eutherian mammal gestation. Marsupials almost invariably have shorter gestational period (12–38 days) than eutherians (16–660 days) (Ferner et al, ). Some reptiles have a gestation period of several months (Gregorovicova et al, ), but the work of the heart, cardiac output and metabolic rate of mammals is several times greater than in similarly sized reptiles (Jensen et al, ).…”
Section: The Anatomy Of the Atrial Septum Of Eutherian Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Already Röse () proposed the secondary foramen was an adaptation to particular conditions of gestation and Runciman and colleagues (Runciman et al, ) suggested a role for the great duration of the eutherian mammal gestation. Marsupials almost invariably have shorter gestational period (12–38 days) than eutherians (16–660 days) (Ferner et al, ). Some reptiles have a gestation period of several months (Gregorovicova et al, ), but the work of the heart, cardiac output and metabolic rate of mammals is several times greater than in similarly sized reptiles (Jensen et al, ).…”
Section: The Anatomy Of the Atrial Septum Of Eutherian Mammalsmentioning
confidence: 99%
“…They also have fur and secrete milk from pores on the belly. Marsupials, like kangaroos, give birth to very immature offspring that complete most of the development in the mother's pouch (Ferner et al, ; Guernsey et al, ). Marsupials are considered a sister group to eutherian mammals (Song et al, ).…”
Section: Evolution Of the Atrial Septummentioning
confidence: 99%
“…The embryonic pulmonary development is different between C. fuliginosus and other American marsupials, but whether these differences persist at birth is unknown. Also, to compare the heart chambers at different stages among marsupial species would be of interest because its closure varies among groups (Ferner et al, 2017;Hughes & Hall, 1988). More samples and thorough anatomical and histological descriptions should help to solve some of the unsolved questions about the life history and evolution of these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although new methods to analyze the relative events in embryology were developed in recent years (Germain & Laurin, ; Werneburg, ), the lack of samples of many mammal species hinders comprehensive analyses (Werneburg et al, ; Werneburg & Sánchez‐Villagra, ). This is true for Paucituberculata, which remains absent from phylogenetic studies that include embryological traits (Ferner, Schultz, & Zeller, ; Freyer, Zeller, & Renfree, ; Werneburg et al, ; Zeller & Freyer, ). Its inclusion can potentially offer relevant information due to its basal position in the marsupial tree (Meredith et al, , but see Bininda‐Emonds et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Here we use micro-computed tomography (lCT) to visualize the skeletal anatomy of several ursid neonates and compare their skeletal maturity levels with those of other caniform outgroup neonates. Although skeletal anatomy has not been explicitly used to assess the relative altriciality of mammalian neonates (Ferner et al 2017), we suggest it is a useful measure of maturity as it is directly connected to the functional aspects of neonatal survival such as locomotion and suckling. lCT imaging offers a non-invasive, highresolution approach to capture the anatomical details of neonate skeletons (Hautier et al 2012;Roston et al 2013;Newton et al 2018).…”
Section: Introductionmentioning
confidence: 99%